ESO Astrophysics Symposia
DOI: 10.1007/978-3-540-74713-0_53
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Probe of the QSO’s Obscured Evolution

Abstract: The obscured phase of QSOs, as well as their accretion history, can be best followed by observing QSOs bright in >10 MeV gamma-rays. By analysing the resonant absorption troughs in spectral energy distribution of flaring QSOs one can measure the (baryonic) absorbing column and baryonic content of the QSO host galaxy, while the flare strength will give information on the accretion rate of the QSO powering supermassive black hole. By measuring the baryonic absorbing column for QSOs at different redshifts one can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In previous works (e.g., Ref. [16]) it has been demonstrated that the direct reactions ( 3 He, 3 He ) and ( 3 He,α) into the same final nucleus do produce very similar decay cascades. Also, the extracted NLD and RSF were found to be equal within the expected fluctuations.…”
Section: Experiments and Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…In previous works (e.g., Ref. [16]) it has been demonstrated that the direct reactions ( 3 He, 3 He ) and ( 3 He,α) into the same final nucleus do produce very similar decay cascades. Also, the extracted NLD and RSF were found to be equal within the expected fluctuations.…”
Section: Experiments and Analysismentioning
confidence: 86%
“…The discovery of the 1157-keV γ -ray line from 44 Ca was reported by Iyudin et al [3], while measurements of the 67.9-and 78.4-keV lines from 44 Sc were presented by Renaud et al [2]. From the combined γ -ray flux, the half-life of 44 Ti, and the distance and age of the remnant, an initial synthesized 44 Ti mass of 1.6 +0.…”
Section: Introductionmentioning
confidence: 91%